2022
DOI: 10.1177/09567976211051744
|View full text |Cite
|
Sign up to set email alerts
|

Melting Ice With Your Mind: Representational Momentum for Physical States

Abstract: When a log burns, it transforms from a block of wood into a pile of ash. Such state changes are among the most dramatic ways objects change, going beyond mere changes of position or orientation. How does the mind represent changes of state? A foundational result in visual cognition is that memory extrapolates the positions of moving objects—a distortion called representational momentum. Here, five experiments ( N = 400 adults) exploited this phenomenon to investigate mental representations in state space. Part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The present results add to the literature investigating the ways that perceiving and remembering interact in the service of constructing visual memories. For example, a central result in visual cognition is that the mind plays forward the movements of objects in memory—a phenomenon called representational momentum (Freyd, 1983; Freyd & Finke, 1984; Hubbard, 2005)—and such effects have recently been extended to surprisingly complex types of change, including changes in the physical states of objects (e.g., melting ice; Hafri et al, 2022). Recent work has even shown that the mind adds vividness to scene images such that the world is remembered in higher definition than it actually appears—a phenomenon called vividness extension (Rivera-Aparicio et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The present results add to the literature investigating the ways that perceiving and remembering interact in the service of constructing visual memories. For example, a central result in visual cognition is that the mind plays forward the movements of objects in memory—a phenomenon called representational momentum (Freyd, 1983; Freyd & Finke, 1984; Hubbard, 2005)—and such effects have recently been extended to surprisingly complex types of change, including changes in the physical states of objects (e.g., melting ice; Hafri et al, 2022). Recent work has even shown that the mind adds vividness to scene images such that the world is remembered in higher definition than it actually appears—a phenomenon called vividness extension (Rivera-Aparicio et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, perception in some cases appears to generate representations of relations at an abstract, structured level (for a review, see Hafri & Firestone, 2021). This project also joins an emerging literature exploring the interface between language and visual cognition, and how they share surprisingly sophisticated content and representational principles (Cavanagh, 2021; Hafri et al, 2018, 2020; Hafri, boger, et al, 2022; Strickland, 2017). Of course, one caveat to our claims about the visual system’s precise role in the linguistic-visual mapping is that a stimulus being visual does not on its own entail that all of its high-level properties (such as symmetry) are perceived via rapid, automatic visual processes.…”
Section: Discussionmentioning
confidence: 95%
“…[4,[24][25][26][27][28]) and link to similar perceptual expectations when observing changes in physical (non-social) scenes (e.g. gravity [53]; transitions between object states [41,42]). These findings therefore provide an important advance to our understanding of the underlying mechanisms of social perception.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 38 ] developed a novel experimental paradigm that was able to reveal the prior perceptual expectations that govern social perception and make them visible as a subtle perceptual bias towards what is expected (but not necessarily observed; for similar effects in memory, see [ 39 , 40 ]; outside of social perception, e.g. [ 41 , 42 ]). They hypothesized that the predictions people make of others' behaviour—and which are then tested against the actions that are observed—are governed by the principle of teleology: the assumption that people's behaviour is fundamentally goal directed, and that it will be actioned in the most rational and energy-efficient way [ 2 , 3 , 43 ].…”
Section: Introductionmentioning
confidence: 99%